2016
DOI: 10.1038/srep32975
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression clines reveal local adaptation and associated trade-offs at a continental scale

Abstract: Local adaptation, where fitness in one environment comes at a cost in another, should lead to spatial variation in trade-offs between life history traits and may be critical for population persistence. Recent studies have sought genomic signals of local adaptation, but often have been limited to laboratory populations representing two environmentally different locations of a species’ distribution. We measured gene expression, as a proxy for fitness, in males of Drosophila subobscura, occupying a 20° latitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 92 publications
(130 reference statements)
1
19
0
Order By: Relevance
“…Reanalyzing clinal population genetic data (Sedghifar, Saelao, Begun 2016), SNF4Aγ is among the 603 most differentiated genes shared by North American and Australian D. simulans populations. Gene expression of SNF4Aγ is clinal in European D. subobscura populations, with southern populations having lower expression levels (Porcelli et al 2016), which parallels the response observed in our experimental evolution populations. Because the selected haplotype may be partially maintained in other populations, we tested the diagnostic SNPs for clinal variation.…”
Section: Ampk Explains the Phenotypic Changes Observed In Hot Evolvedsupporting
confidence: 84%
See 2 more Smart Citations
“…Reanalyzing clinal population genetic data (Sedghifar, Saelao, Begun 2016), SNF4Aγ is among the 603 most differentiated genes shared by North American and Australian D. simulans populations. Gene expression of SNF4Aγ is clinal in European D. subobscura populations, with southern populations having lower expression levels (Porcelli et al 2016), which parallels the response observed in our experimental evolution populations. Because the selected haplotype may be partially maintained in other populations, we tested the diagnostic SNPs for clinal variation.…”
Section: Ampk Explains the Phenotypic Changes Observed In Hot Evolvedsupporting
confidence: 84%
“…Temperature is a major factor modulating the expression of numerous genes in ectotherms and is particularly well studied in Drosophila (Zhao et al 2015; Chen, Nolte, Schlötterer 2015; Porcelli et al 2016). Our experimental populations, which evolved in a novel hot thermal environment displayed highly significant differences in gene expression involving many genes of well-defined pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously found, across six D. subobscura populations from a 20°latitudinal cline in Europe (of which the Valencia and Uppsala populations represent the southern-and northernmost population, respectively), a gradient in gene expression in which adult males from southern populations have higher expression of spermatogenesis genes than males from northern populations, under benign (18°C) conditions (Porcelli et al, 2016). Given that females are monandrous, sperm competition cannot explain increased investment in spermatogenesis in lower latitude populations.…”
Section: Discussionmentioning
confidence: 98%
“…To characterize gene expression in D. athabasca we analyzed EB RNA--seq data from whole larva and pooled larval heads (above , Table S1). For D. subobscura we analyzed RNA--seq data generated from two pools of whole individuals (Uppsalapool and Valenciapool; Porcelli et al 2016). For each species, all reads were aligned to their respective reference genomes using HiSat2 (Kim et al 2015) and StringTie (Pertea et al 2015) was used to estimate gene expression (FPKM).…”
Section: Gene Expression Analysesmentioning
confidence: 99%